Rapeseed Cake Valorization into Bioplastics Based on Protein Amyloid Fibrils. Issue 3 (17th October 2022) - Bagnani, Massimo; Ehrengruber, Silas; Soon, Wei Long; Peydayesh, Mohammad; Miserez, Ali; Mezzenga, Raffaele
Abstract: Biodegradable polymers obtained from renewable resources are urgently needed to help mitigating the environmental burden of plastic pollution. Herein, a green process is developed to obtain protein‐based bioplastics through valorization of rapeseed cake. First, the effects of different protein extraction protocols are investigated, including water extraction at pH values from 1 to 12 and salt extraction with isoelectric point precipitation (IP), on proteins profile and sample composition. It is demonstrated that alkaline extraction at pH 12 results in the highest extraction yields of proteins (≈70%) and total solutes (≈50%). The IP results in lower yields but in highest protein purity of ≈80%. Alkaline extraction at pH 10.5 results in the extraction of 36% total solutes and ≈50% of proteins, with a protein profile similar to that obtained by IP, rich in α and β polypeptides chains of cruciferin. AFM analysis shows that samples containing cruciferin allow self‐assembly into mature amyloid fibrils upon incubation. Rapeseed amyloids are blended with polyvinyl alcohol and glycerol to develop bioplastics films that are characterized by decreased water absorption, higher water contact angle, and elongation at break >600%, more than double compared to films obtained from native monomers. Abstract : Plastic pollution is a major global threat and sustainable alternatives are urgently needed. Proteins, obtained from food wastes, offer unique possibilities to develop functional bioplastics, whose properties can be enhanced by transforming native proteins in self‐assembled amyloid fibrils. Amyloids can be combined with biodegradable polymers for developing green composite materials.